ISOLATED PLEURAL FLUID LACTIC DEHYDROGENASE LEVEL: A COST EFFECTIVE WAY OF CHARACTERIZING PLEURAL EFFUSIONS - Iqbal, Mobeen; Jaffery, Tara; Shah, Sajid H (Journal of Ayub Medical College Abbottabad, 2002)
Background: Characterization of pleural effusion into an exudate or transudate is usually the first step in diagnostic evaluation. Light's criteria have been universally accepted as gold standard in this regard. We wanted to see the utility of isolated pleural fluid lactic dehydrogenase level (representing one of Light's classical criteria) in characterizing pleural effusion in our setting. We also wanted to compare the accuracy of commonly used conventional criteria with Light's criteria of isolated pleural fluid lactic dehydrogenase. Methods: Patients who underwent diagnostic thoracentesis for one-year period were studied. Characterization of pleural effusions using biochemical criteria including pleural fluid protein, lactic dehydrogenase level (LDH), red blood cell (RBC) count and white blood cell (WBC) count were identified and compared with pre-determined clinical criteria (gold standard). For each biochemical criteria sensitivity, specificity, positive predictive value and negative predictive value were calculated. Results: Sixty-two patients underwent diagnostic thoracentesis. Sixteen were excluded, as they did not fulfill pre-determined clinical criteria. Eight patients had transudative effusion vs. 38 exudates. LDH was found to be the most sensitive (97.2%) while WBC> 1000/mm3 was the most specific (100%) of all the criteria looked at. The overall accuracy was highest for Light's criteria of isolated LDH>200 IU/litre (95.6%) followed by pleural fluid protein, WBC count and RBC count. Conclusion: We conclude that isolated pleural fluid LDH, as a representative of classical Light's criteria, is the most accurate criteria for characterizing pleural effusions. Due to its low accuracy isolated pleural fluid protein should not be ordered routinely. This approach may result into potential cost savings in our economically restraint society. Key words: Pleural effusion, exudate, lactic dehydrogenase,